Benchmarking the philosophy of Nigerian policy on education with the United Nations’ sustainable development goals and traditional ethical principles of the social doctrine of the Catholic Church - Chidozie, Ihekwoaba Michael Festus (Strathmore University, 2018)
This dissertation seeks to benchmark the philosophy of Nigeria’s education policy with the United Nations’ sustainable development goals as well as the traditional ethical principles of the social doctrine of the Catholic Church, with the primary aim of identifying where there is a total, partial or zero relation for a possible improvement of Nigeria’s education policy philosophy. Igbuzor (2006) in stressing the importance of education stated that “Education is a human right that should be accorded to all human beings solely by reason of being human”.The utmost importance attached to education in Nigeria was clearly emphasized in the National Policy on Education (NPE, 2004). The Federal Republic of Nigeria, in this policy, adopted education as an instrument "par excellence" for effecting national development. But despite the government's commitment to education, the quality of education in Nigerian schools has been declining tremendously, thereby giving successive government's serious concern. The question has become, what is wrong with the Nigeria educational system? The investigation utilized a philosophical approach that leverages on a personalistic anthropology which underscores the centrality of the person as the primary focus of investigation. This involves the systematic identification, location, and analysis of documents containing information related to the research problem. The researchers use the information derived to evaluate whether the philosophy of Nigerian education policy can be improved.While the results of the benchmarking of the philosophy of Nigeria’s education policy against the United Nations’ development goals as well as the traditional ethical principles of the social doctrine of the Catholic Church were highlighted, the findings revealed that there are areas where the NPE philosophy needs partial and total improvement at the same time.
Thesis submitted in partial fulfillment of the requirements for the Degree of Masters in Applied Philosophy and Ethics (MAPE) at Strathmore University, Kenya
Keywords: National Policy on Education; Nigeria’s Education Policy; Sustainable Development Goals; Nigeria Educational System; Social Doctrine -- Catholic Church